2020
DOI: 10.1101/2020.08.30.20184697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and predictors of depression, anxiety and stress symptoms among pregnant women during COVID-19-related lockdown in Abakaliki, Nigeria

Abstract: Introduction: Several studies on COVID-19 and pregnancy have been published recently, but few studies have evaluated the impact of this pandemic on maternal mental health particularly in low-resource setting. Aim: To determine the prevalence and predictors of COVID-19-related depression, anxiety and stress symptoms among pregnant women. Materials and methods: This was a questionnaire-based cross-sectional study conducted among 456 pregnant women attending prenatal care at Abakaliki, Nigeria during COVID-19-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
64
5
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(85 citation statements)
references
References 13 publications
9
64
5
7
Order By: Relevance
“…The possible explanation might be because of the higher transmission rates of COVID in India, Canada, and Iran, which lead to high depression in HIV-positive pregnant women. 33 , 34 The finding of the study was also lower than the study conducted in Nigeria (45.2%) 35 and across European countries (15%). 27 The possible explanation may be due to the time gap for access to COVID-19-related information.…”
Section: Discussioncontrasting
confidence: 62%
“…The possible explanation might be because of the higher transmission rates of COVID in India, Canada, and Iran, which lead to high depression in HIV-positive pregnant women. 33 , 34 The finding of the study was also lower than the study conducted in Nigeria (45.2%) 35 and across European countries (15%). 27 The possible explanation may be due to the time gap for access to COVID-19-related information.…”
Section: Discussioncontrasting
confidence: 62%
“…In South Africa the prevalence is particularly high, with several studies reporting that one in every three pregnant women develop symptoms of depression, and one in every four pregnant women develop symptoms of anxiety [46,47,48]. This report by Nwafor et al [28] is however, similar to studies conducted on the psychological effects of the SARS outbreak in 2003 on the experience of pregnant women, that showed that these women experienced high levels of depression, anxiety and stress with regards to potential infection. Anxiety is common during and after pregnancy as women anticipate and adjust to motherhood, especially in those women and couples who have previously experienced adverse pregnancy outcomes, such as miscarriage and perinatal death [49,50].…”
Section: Discussionmentioning
confidence: 87%
“…In the study conducted by Nwafor et al [28], the study reported severe and extremely severe depression in 7.2% (n=33) and 6.4% (n=29) of participants. Analysis also revealed that 3.3% (n=15) and 7.7% (n=35) of women had severe and extremely severe anxiety, respectively.…”
Section: Studies Conducted In Africamentioning
confidence: 92%
See 2 more Smart Citations